POSISI STRATEGIS DAN ARAH PENGEMBANGAN UNIT PELAKSANA TEKNIS DINAS (UPTD) MENJADI BADAN LAYANAN UMUM DAERAH (BLUD) DI PEMERINTAH PROVINSI JAWA TIMUR - Slamet Hari Sutanto (Department of Public Administration, Universitas Negeri Surabaya, 2018)
With all the limitations of the current government budgeting system, not all government affairs and development to realize the welfare for the people can not may be all financed by APBD. East Java provincial government is currently pushing the Regional Technical Implementation Unit (UPTD) in SKPD environment began to use financial management system Regional Public Service Agency (BLUD). The policy is clearly stated in East Java Fiscal Policy Innovation Roadmap 2014-2019. The purpose of this study is to (1). To identify the condition of UPT-UPT in East Java Provincial Government (2). Identify the problems and challenges faced in developing the UPTD into BLUD and (3). To formulate development strategy that can be done by East Java Provincial Government in developing UPTD become BLUD. The research method used is mixed method that combines qualitative data analysis with quantitative data using SWOT matrix, then to determine the strategic position and direction of development is done through analysis of General Electrics (GE) matrix. Population in this research is all Technical Implementation Unit (UPT) in East Java Provincial Government, while the sampling is done pursuant to purposive sampling. The results showed (1). UPT such as UPT P2SKP Mayangan, UPT P2SKP Pondokdadap, UPT P2SKP Muncar, and UPT PSMB-LT ready if improved status becomes BLUD see the factor of financial ability, completeness of facilities and infrastructure and its potentials (2). Some UPTs such as UPT PB Palawija, UPT PB Holtikultura, and UPTIK Timber can be upgraded to BLUD, but need to be prepared in advance, especially supporting infrastructure, especially technology aspects of technology and supporting human resources, as well as capital and promotion to develop into wider market. (3). While the Training Unit (BLKI) of Singosari and Jember, due to the specific service characteristic and the special service segment so that the dependence on the APBD/APBN is still very high, it is still difficult in terms of its existence to be upgraded to PPK BLU/BLUD.